Thrombosis risk associated with COVID-19 infection. A scoping review. Issue 192 (August 2020) - Al-Ani, Fatimah; Chehade, Samer; Lazo-Langner, Alejandro
Abstract: Background: Infection by the 2019 novel coronavirus (COVID-19) has been reportedly associated with a high risk of thrombotic complications. So far information is scarce and rapidly emerging. Methods: We conducted a scoping review using a single engine search for studies assessing thrombosis and coagulopathy in COVID-19 patients. Additional studies were identified by secondary review and alert services. Results: Studies reported the occurrence of venous thromboembolism and stroke in approximately 20% and 3% of patients, respectively. A higher frequency seems to be present in severely ill patients, in particular those admitted to intensive care units. The thrombotic risk is elevated despite the use of anticoagulant prophylaxis but optimal doses of anticoagulation are not yet defined. Although an increase of biomarkers such as D-dimer has been consistently reported in severely ill COVID-19, the optimal cut-off level and prognostic value are not known. Discussion: A number of pressing issues were identified by this review, including defining the true incidence of VTE in COVID patients, developing algorithms to identify those susceptible to develop thrombotic complications and severe disease, determining the role of biomarkers and/or scoring systems to stratify patients' risk, designing adequate and feasible diagnostic protocols for PE, establishing the optimal thromboprophylaxis strategy, and developing uniform diagnostic and reporting criteria. Highlights: Thrombotic events, venous and arterial are frequent in COVID-19, more so in critically ill patients. Valid biomarkers to define risk and prognosis are still lacking. Anticoagulant prophylaxis is needed in all patients. The role of higher doses of anticoagulants in all patients is unclear. There is a need to develop standard clinical definitions, common data elements, and standard reporting criteria.